Reward Management : Alternatives, Consequences and Contexts. - Jones, Sarah E.; Perkins, Stephen J.; Perkins, Stephen J.; Chartered Institute of Personnel and Development (London : KoganPage, 2020)
This textbook completely maps to the CIPD module of the same name and is also ideal for students on reward modules on wider HR or business degree programmes. It provides international case studies and examples, and links to practical tools via end-of-chapter web links.
Previous edition: published as by Stephen J. Perkins, Geoff White and Sarah Jones. London: Chartered Institute of Personnel and Development, 2016.
At foot of title: CIPD.
Includes bibliographical references and index.
Keywords: Compensation management; Performance awards; Business and Management